Extending the functionality of topologies of Web-oriented control systems for technological objects based on “Open User Communication” - Zamikhovskyi, Leonid; Nykolaychuk, Mykola; Levytskyi, Ivan (Eastern-European Journal of Enterprise Technologies, 2025)
This study focuses on the information processes involved in the interaction between components of WEB-oriented control systems based on the “Open User Communication” (OUC) technology. The task addressed related to the violation of data consistency across different topology levels in process control systems during cyclic server requests, the need for batch transmission of heterogeneous data types, the unification of equipment, and the technical validation of solutions. A system topology has been designed using a SCADA (Supervisory Control and Data Acquisition) system, a server PLC (Programmable Logic Controller), and four terminal PLCs with integrated OUC in the “TIA Portal” environment. This topology allows for data consistency between the server and terminal PLCs by transmitting heterogeneous data formats within a single frame using dynamic data-slice selection. Hardware tools and application software were developed in the Function Block Diagram (FBD) language of the IEC 61131-3 standard to implement “Open User Communication” with transmission capacities of up to 8192 bytes per frame. To study information processes, a simulation model of interaction between the server and terminal PLCs based on OUC was built and tested using virtual PLC simulators with dynamic data-slice adjustment. The transmission of 12 different data formats (a total of 332 bytes) was tested using the “TSEND_C” and “TRCV_C” instructions under a “monitoring-on” mode. GRE tunneling protocol parameters were configured to enable simultaneous data exchange between the server and terminal PLCs via “Open User Communication”, alongside PLC programming via “S7-Communication”. Based on the proposed solutions, a WEB-oriented data acquisition system for technological facilities of municipal water-supply enterprises was developed and validated under industrial conditions